Here be Heathens: The Supernatural Image of Northern Fenno-Scandinavia in Pre-Modern Literature - Perabo, Lyonel D., 1989- (2016)
The present thesis involves a study of the various ways in which the Northernmost regions of Fenno-Scandinavia and their inhabitants were depicted as being associated with the supernatural in pre-Modern literature. Its findings are based on an exhaustive study of the numerous texts engaging with this subject, ranging from the Roman era to the publication of the Historia de Gentibus Septentrionalibus of Olaus Magnus in 1555. The thesis presents and analyses the most common supernatural motifs associated with this Far-Northern area, which include animal transformation, sorcery and pagan worship, as well as speculating about their origins, and analyzes the ways in which such ideas and images evolved, both over time and depending on the nature of the written sources in which they appear. The author argues that Northern Fenno-Scandinavia was thought of as a wild, supernatural and pagan land because of the differences in languages, ways of living and magical practices of its inhabitants, an image partially mirrored in literary texts, some of which are of considerable antiquity. The thesis also notes the way in which the supernatural images associated with the Sámi and Finnic peoples seem to have also become attached to the other Germanic-related people living in the north of Norway, who are also often depicted as supernatural “others” equipped with supernatural or magical skills in the literature. Þessi ritgerð fjallar um þá margvíslegu máta sem nyrstu svæði Fennóskandíu og íbúum þess var lýst í tengslum við yfirnáttúruleg öfl í for-nýaldarbókmenntum. Niðurstöðurnar eru byggðar á ítarlegri rannsókn á fjölda texta sem fjalla um viðfangsefnið, allt frá Rómaveldi til útgáfu Historia de Gentibus Septentrionalibus eftir Olaus Magnus í 1555. Ritgerðin kynnir og greinir helstu minni yfirnáttúrulegra afla sem tengjast þessu norðlæga svæði, til að mynda hamskiptingar, galdra og blót. Tilgátur um uppruna þeirra koma fram og farið er í saumana á því hvernig hugmyndirnar gætu hafa komið fram og þróast, eftir því sem tíminn leið ...